An Augmented ABCA4 Screen Targeting Noncoding Regions Reveals a Deep Intronic Founder Variant in Belgian Stargardt Patients. Issue 1 (January 2015) - Bauwens, Miriam; De Zaeytijd, Julie; Weisschuh, Nicole; Kohl, Susanne; Meire, Françoise; Dahan, Karin; Depasse, Fanny; De Jaegere, Sarah; De Ravel, Thomy; De Rademaeker, Marjan; Loeys, Bart; Coppieters, Frauke; et al.
<x xml:space="preserve">Abstract</x> A and B: The deep intronic ABCA4 variant V4 (c.4539+2001G>A), which has a predicted effect on splicing, occurs in almost 26% of a Belgian STGD1 cohort with one identified coding mutation. It is part of a shared haplotype block in these patients, indicative for a founder mutation. C. V4 has a moderate‐to‐severe effect on the STGD1 phenotype. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>